Answer: 40
Step-by-step explanation: 60/3= 20 20x3= 60 20x2=40
Answer:
Assuming you mean (2^3)3, the answer is 24
Step-by-step explanation:
using pemdas you do 2 to the third power first
2x2=4 4x2=8
then you mutiply by the number not in parenthesis; 3
8x3 = 24
F(x) = sqrt(x^2 + 3) ; g(x) = sqrt(X-2)
f(g(x))= √[{√(x-2)²+3}]
=√[{x-2+3}]
√(x+1)
C
Since this creates a 45-45-90 triangle, we know they are equal since the legs of 45-45-90 triangles are congruent
3x+35°-10
remove the parentheses so the equation is
x+ 15°+x+20°+(x-10)